Penegakan Hukum Terhadap Praktik Modifikasi Kendaraan Bermotor Berdasarkan Undang Undang No 22 Tahun 2009 Tentang Lalu Lintas Dan Jalan Raya - Haryo Herjuno Bintang Panji Kusumo; Hermanto Silalahi; Celina Tri Siwi K. (Universitas Katolik Widya Karya Malang, 2024)
Based on the analysis of data and facts obtained by the author directly from the Batu City Transportation Agency, the author concludes that law enforcement carried out by the Batu City Transportation Agency is in the form of strict action not to issue a waybill and a vehicle inspection certificate for vehicles that have been modified where the action is intended that the owner of the motor vehicle cannot use his vehicle to be driven on the highway, with the practice of modification, the Transportation Agency conducted a joint operation with the Police with the aim of providing ticket sanctions to drivers who are proven to have been modified which endangers public safety on the highway as a public road. For the method used, using the empirical juridical method where this method is carried out by observation and data collection by interviewing the targeted respondents. The author's suggestion is that with the violation of the practice of modification of motor vehicles that experience changes in the shape of the vehicle so that it can result in accidents that cause loss of life and material losses. With the Batu City Transportation Agency making a pamphlet to warn that modifications made to motor vehicles, especially goods transport vehicles, can endanger the public and cause accidents. Routine joint operation activities carried out by the Transportation Agency and assisted by the Police in the hope of reducing modification practices because vehicle owners who have been modified are subject to fines by the Police and vehicles cannot re-apply for vehicle inspection certificates that are renewed every 5 years at the Batu City Transportation Agency, East Java.